Robotic-assisted proximal gastrectomy using the double-flap technique for early gastric cancer with situs inversus totalis: a case report - Atsushi Takeno; Toru Masuzawa; Shinsuke Katsuyama; Kohei Murakami; Kenji Kawai; Yoshiteru Katsura; Yoshiaki Ohmura; Yoshinori Kagawa; Yutaka Takeda; Taishi Hata; Kohei Murata (Surgical Case Reports)
Abstract Background The robotic system has been applied in the treatment of gastric cancer (GC), and the procedure has been found to be safe and feasible. Situs inversus totalis (SIT) is a relatively rare autosomal recessive congenital anomaly. We successfully performed robot-assisted proximal gastrectomy (RAPG) and handsewn double-flap esophagogastrostomy for GC in a patient with SIT. Case presentation A 71-year-old woman was referred to us with an asymptomatic ulcerative lesion in the upper body of the stomach. Computed tomography revealed that she had SIT. She was diagnosed with cT1bN0M0, cStageIA gastric cancer. RAPG with lymph node dissection and handsewn double-flap esophagogastrostomy was performed. Robotic surgery enabled the surgeon to perform the surgery without changing his position and experiencing any confusion resulting from the patient’s reversed anatomy. It took 448 min, and no intraoperative complications occurred. Her postoperative course was uneventful; she was discharged on postoperative day 10. The final pathologic report showed pT1b1N0M0, pStage IA. Conclusions This is the first case describing RAPG with handsewn double-flap esophagogastrostomy for a SIT patient with early GC.